The Effect of Giving Sorghum on the Growth of Native Chickens Aged 3-10 Weeks - Matius Ngura Bili; Ni Ketut Sri Rukmini; Ni Made Yudiastari (Warmadewa University Press, 2022)
Native chicken farms in Indonesia at this time have experienced very rapid development. One of the poultry that is currently being developed in Indonesia is the Super kampung chicken. The current reality is that the price of commercial feed in the market is felt by farmers to be very expensive, while feed is the largest component in poultry farming, where the cost of feed can reach 60-70% of the total production cost, so it is very important to look for other alternative feeds in the availability of ration feed ingredients. to keep production costs as small as possible without reducing optimum production. The use of sorghum seeds in the ration of super native chicken is (substitute) for corn because its nutritional content is almost the same as corn. The design used in this study was a completely randomized design (CRD) which consisted of 5 treatments and 3 replications. S0 (Control) of chickens that were not given sorghum, S1 of chickens that were fed a diet containing 7.5% sorghum, S2= 15%, S3= 22.5% and S4= 30%. The arrangement of the 3-story cage with a total of 15 plots, each containing 5 chickens, so that 75 chickens were used with a body weight range of 183.2-210.0 g. From the results of the study, the administration of various levels of sorghum did not have a significant effect (P>0.05) on final body weight, weight gain, ration consumption, and ration conversion of super-village chickens aged 3-10 weeks. In the administration of various levels of sorghum at S0 (Control) it was higher than the S1, S2, S3, and S4 treatments on final body weight, weight gain, ration consumption, and ration conversion for super free-range chickens aged 3-10 weeks.